Fruit and vegetable processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Fruit and vegetable processing by Mircea Enachescu Dauthy 1995 381pp ISBN 92 5 1036578